2008
DOI: 10.1126/science.1161151
|View full text |Cite
|
Sign up to set email alerts
|

PirB is a Functional Receptor for Myelin Inhibitors of Axonal Regeneration

Abstract: A major barrier to regenerating axons after injury in the mammalian central nervous system is an unfavorable milieu. Three proteins found in myelin--Nogo, MAG, and OMgp--inhibit axon regeneration in vitro and bind to the glycosylphosphatidylinositol-anchored Nogo receptor (NgR). However, genetic deletion of NgR has only a modest disinhibitory effect, suggesting that other binding receptors for these molecules probably exist. With the use of expression cloning, we have found that paired immunoglobulin-like rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
457
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(476 citation statements)
references
References 23 publications
18
457
1
Order By: Relevance
“…This is a phenomenon that is frequently observed when comparing acute interventions with constitutive KOs where compensatory mechanisms are often activated. These results are also in line with the proposed role of NogoA and NgR1 in regulating the stabilization of neuronal circuits and in inhibiting structural rearrangements and thereby limiting, e.g., spinal cord, or ocular dominance (OD) plasticity (9,27,30,31), or regulating the formation of long-lasting memories (15).…”
Section: Discussionsupporting
confidence: 72%
“…This is a phenomenon that is frequently observed when comparing acute interventions with constitutive KOs where compensatory mechanisms are often activated. These results are also in line with the proposed role of NogoA and NgR1 in regulating the stabilization of neuronal circuits and in inhibiting structural rearrangements and thereby limiting, e.g., spinal cord, or ocular dominance (OD) plasticity (9,27,30,31), or regulating the formation of long-lasting memories (15).…”
Section: Discussionsupporting
confidence: 72%
“…Given that LGI1 is critically important for glutamatergic synapse maturation and dendritic pruning (Zhou et al, 2009), determining whether LGI1, NgR1 and ADAM22 function collaboratively to drive synapse maturation and dendritic sculpting is a key priority for future studies. Mice lacking PirB (Atwal et al, 2008), a recently identified receptor for Nogo, MAG, and OMgp, also display supranormal experience-driven plasticity, and it is conceivable that PirB may function in similar pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies questioned the importance of NgR1 in chronic growth inhibition mediated by myelin ligands [24] and confirmed only partially the regeneration promoting action of NEP1-40 [25]. All three NgR1 ligands bind to a second receptor, PirB, which is also implicated in neuronal regeneration [26]. These results further add to the complexity of neurite outgrowth inhibition in the CNS.…”
Section: Introductionmentioning
confidence: 68%